What is “The End of Nature”?: Modernity and Ambivalent Heterotopias - Gutauskas, Mintautas (Filosofia, 2019)
The paper aims to clarify the meaning of the diagnosis ‘the end of nature’, which Anthony Giddens distinguishes as the most important characteristic of late modernity. This view assumes that modernity frames our questions about nature in such a way that makes them appear as a problem of control. Revealing the manner of this framing is the paper’s major objective. It begins with an examination of the meaning of the end of nature as a diagnosis announced by McKibben and Giddens; then it seeks to foreground the roots of modern outlook in modernity, which shaped self-reflective thinking; and moves to an analysis of the structures of high modernity as described by Giddens. The reflexivity of modern institutions, the disembedding of time and space, and the colonisation of nature are distinguished as the aspects that most crucially determine contemporary attitudes towards nature. The paper concludes that the end of nature should not be understood as the decay of natural territories and species but, rather, as the absolute hegemony of modern outlook so that even the territories of wilderness are managed in terms of internally reflexive modern systems. The territories of wild nature turn into ambivalent heterotopias subjected to modern protection and control, both of which, in the Anthropocene epoch, turn out to be limited and questionable approaches.